(untitled) (Malaysian Management Journal, 1995)
The study empirically tests the hypothesis that firms try to maintain or improve their ranks. Malaysian data is used. The findings of the study indicate that; 1) companies, in general, try to maintain or improve their relative ranks in the corporate structure over time; 2) smaller and larger companies are more concerned about maintaining their ranks in the corporate hierarchy; 3) companies are more concerned with maintaining their ranks in the short run than in the long run; 4) the concentration of wealth and monopoly power of the largest eleven companies declined over the years as more companies were listed and mailer companies improved their positions in the industry; and 5) there is a non-significant relationship between asset-size and profitability of the firm, at least in the short run. However, the study indicates that in the long run, rank maintenance and profit maximization are complementary hypotheses.